A NEED ASSESSMENT OF ETHICS COURSE FOR PRIMARY CARE PHYSICIAN: PHYSICIANS' PERSPECTIVE IN YOGYAKARTA PROVINCE, INDONESIA - Nurrokhmanti,, Hikmawati; Heru, Adi; Joseph, Hari Kusnanto (Universitas Gadjah Mada, 2023)
Background: Primary care physicians, as first-line doctors, deal with ethical cases that challenge them to make the best patient decisions. Helping primary care physicians to be more aware of ethical cases and the process of case decision-making will improve all stakeholder's needs. Physician standard opinion on the best decision for their patient will be the baseline of suited training for them.Methods: We conducted a mixed-method study to understand GP decisions regarding certain ethical cases. In the quantitative phase, we used and presented several standardized ethical cases with several